Analisis terhadap Putusan PA Koto Baru Nomor 18/Pdt.P/2025/PA.Kbr tentang Penolakan Dispensasi Nikah Pasca Khalwat Perspektif Sadd Adz-Dzari’ah - Yudia Permata Sari; Maizul Imran (Lembaga Yasin AlSys, 2026)
Although marriage dispensation has received considerable attention in various studies of Islamic family law, research specifically examining the rejection of marriage dispensation following khalwat from the perspective of sadd al-dzari’ah remains limited. This study aimed to analyze the judge’s considerations in Koto Baru Religious Court Determination Number 18/Pdt.P/2025/PA.Kbr concerning the rejection of marriage dispensation following khalwat and to examine the determination from the perspective of sadd al-dzari’ah. The study employed a qualitative approach with a legal case study design. Data were obtained through observation, semistructured interviews with the judge who handled the case, and documentation comprising the court determination and relevant laws and regulations. The data were analyzed using qualitative descriptive analysis through the stages of data reduction, data display, and conclusion drawing. The findings showed that the rejection of marriage dispensation was based on the applicants’ failure to meet the minimum marriage age, the psychological immaturity of the prospective spouses, the protection of children’s rights, and the absence of urgent grounds as stipulated in Supreme Court Regulation Number 5 of 2019. From the perspective of sadd al-dzari’ah, the judge’s determination reflected an effort to block avenues that could potentially cause greater harm in order to realize public benefit and child protection. This study confirms that judicial considerations in marriage dispensation cases are oriented not only toward formal legal aspects but also toward preventing harm and fulfilling the best interests of the child. These findings contribute to the development of Islamic family law studies, particularly regarding the application of sadd al-dzari’ah in resolving marriage dispensation cases, and imply the importance of judicial consistency in prioritizing the principles of child protection and public benefit in every examination of a marriage dispensation application.